PENGARUH LABA PER LEMBAR SAHAM, NILAI BUKU PER LEMBAR SAHAM, DAN TRANSAKSI ABNORMAL PIHAK BERELASI TERHADAP RELEVANSI NILAI DENGAN MEKANISME TATA KELOLA PERUSAHAAN SEBAGAI VARIABEL MODERASI - Chuswatul Chasanah; Endang Kiswara (Diponegoro Journal of Accounting, 2017)
The purpose of this study is  to get empirical evidence about the effect of earnings per share, book value per share, and abnormal related party transaction on value relevance. Independent variables in this study is the earnings per share, book value per share, and abnormal related party transactions, while the dependent variable is the value relevance. The population of this research is non-financial companies listed on the Indonesia Stock Exchange in 2011 until 2015. The sampling method is using stratified random sampling and obtained a sample of 185 companies. Data analysis was performed with the classical assumption and hypothesis testing and regression analysis. Statistical research program using SPSS version 23. The results of this study indicate that there is a negative and insignificant relationship between earnings per share by value relevance, and alsobecame insignificant after moderated by corporate governance. Likewise on the relationship between the book value per share by value relevance, there is a positive and significant relationship, but later became insignificant after moderated by corporate governance. Abnormal related party transactions is negative and insignificant related to the relevance value, the results were the not same when moderated by corporate governance. The implications of this study indicate that earnings per share and book value per share are have value relevant. And abnormal related party transactions not reduce the level of value relevance, but corporate governance restrain abnormal related party transactions.